2015
DOI: 10.1093/ofid/ofv018
|View full text |Cite|
|
Sign up to set email alerts
|

Switch to Rilpivirine/Emtricitabine/Tenofovir Single-Tablet Regimen of Human Immunodeficiency Virus-1 RNA-Suppressed Patients, Agence Nationale de Recherches sur le SIDA et les Hépatites Virales CO3 Aquitaine Cohort, 2012–2014

Abstract: We evaluated the efficacy and tolerability of a single-tablet regimen strategy in 304 HIV-1 virologically suppressed patients switching to RPV/FTC/TDF for adverse events or treatment simplification. This strategy maintained virologic suppression and was associated with improved tolerability after 12 months follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
19
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 28 publications
(33 reference statements)
6
19
7
Order By: Relevance
“…The most frequent adverse event leading to discontinuation was renal impairment (5.5%), followed by gastrointestinal intolerance (4.8%). These findings differ from those published by other authors, who found that the most frequent adverse events were neurological disorders and gastrointestinal toxicity …”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The most frequent adverse event leading to discontinuation was renal impairment (5.5%), followed by gastrointestinal intolerance (4.8%). These findings differ from those published by other authors, who found that the most frequent adverse events were neurological disorders and gastrointestinal toxicity …”
Section: Discussioncontrasting
confidence: 99%
“…The main reason for switching to RPV/FTC/TDF was simplification of ART and cost reductions (53.4% of patients). This result is consistent with other studies (49.2%‐73.7%). In all cases, these reasons were followed by occurrence of adverse events with the previous ART regimen, as it was also observed in this study.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations